Economic Turbulence in the Iron Kitchenware Industry in Italy - Garbelli, Maria (European Scientific Journal, ESJ, 2018)
Companies in turbulent economies are required to face several difficulties, mainly related to the specific features of an extremely volatile environment. Although a similar, hypercompetitive context can be considered a global condition today, it is not perceived in the same way worldwide. Thus, international development could be the best method for exporting to different locations and getting the best opportunities to survive in this unstable environment. Italy is one of the European Union countries affected the most by turbulence and the financial crisis with a loss of competitiveness compared to other countries in the Union. The economic system has changed considerably, rising the bankruptcy cases and lowering reported earnings. This paper claims to give an overview of the Italian situation inside the European Community as Italy is recognized as one of the most industrialized areas of northern Italy; the province of Brescia is home of one of the two Italian districts devoted to the iron kitchenware industry—an industry in which Italy held a leading position worldwide for a long time. Ten years after the financial crisis, and supported by exports flows analysis, we evaluate the Italian competitive position in this industry compared to that of the country’s European competitors. Export data (inside and outside the European Union) in three years (2007, 2010, and 2014) show Italy’s leading global role in this industry but also the negative effect of the crisis on the country, witnessed by the strong rise of other competitors.